Tingkat kecemasan terhadap kualitas hidup pada penderita hipertensi usia produktif - Kunoviana, Rizkiyah Diyan; Maliya, Arina (Holistik Jurnal Kesehatan, 2025)
Background: Hypertension is one of the most common non-communicable cardiovascular diseases, especially high blood pressure with systolic pressure ≥140 mmHg and diastolic >90 mmHg. This disease is a global problem and is a major cause of death worldwide. One of the factors causing hypertension is anxiety, such as worry, anxiety, and fear accompanied by physical complaints and health problems. Purpose: To determine the relationship between the level of hypertension anxiety and the quality of life of productive age patients. Method: Quantitative descriptive research involving two variables, namely anxiety level as the independent variable and quality of life as the dependent variable. The study population used were productive age hypertension sufferers in the Gatak Sukoharjo health center area and was carried out on September 5-24, 2024. Sampling using purposive sampling technique and obtained 84 respondents. Results: Most respondents were aged 56-64 years as many as 33 respondents (39.3%), the majority were female 78 (92.9%) and were married as many as 83 respondents (98.8%). The most recent education was only up to Elementary School as many as 34 respondents (40.5%), as a housewife as many as 65 respondents (77.4%). The majority experienced severe anxiety as many as 37 respondents (44.7%) and poor quality of life as many as 49 respondents (58.8%) with a p-value of 0.001 with a correlation coefficient of 0.765. Conclusion: There is a significant relationship between anxiety levels and quality of life in productive age hypertensive patients. Most respondents experienced severe anxiety followed by low quality of life. Suggestion: Hypertensive patients can improve their healthy lifestyle, check their health regularly, especially the physical health dimension, not feel hopeless in living their lives, get closer to God, and communicate with family and neighbors.   Keywords: Anxiety; Hypertension; Productive Age; Quality of Life.   Pendahuluan: Hipertensi merupakan satu dari penyakit kardiovaskular tidak menular yang paling umum, khususnya tekanan darah tinggi dengan sistolik ≥140 mmHg dan diastolic >90 mmHg. Penyakit ini menjadi masalah global dan sebagai penyebab utama kematian di seluruh dunia. Salah satu faktor yang menyebabkan terjadinya hipertensi adalah kecemasan, seperti khawatir, gelisah, dan takut yang disertai keluhan fisik dan gangguan kesehatan. Tujuan: Untuk mengetahui hubungan antara tingkat kecemasan dan kualitas hidup pasien hipertensi usia produktif. Metode: Penelitian deskriptif kuantitatif yang melibatkan dua variabel yaitu tingkat kecemasan sebagai variabel independen dan kualitas hidup sebagai variabel dependen. Populasi penelitian yang digunakan adalah penderita hipertensi usia produktif di wilayah puskesmas Gatak Sukoharjo dan dilaksanakan pada tanggal 5-24 September 2024. Pengambilan sampel menggunakan teknik purposive sampling dan didapatkan sebanyak 84 responden. Hasil: Sebagian besar responden berusia 56-64 tahun sebanyak 33 responden (39.3%), mayoritas perempuan 78 (92.9%) dan berstatus menikah sebanyak 83 responden (98.8%). Pendidikan terakhir paling banyak hanya sampai Sekolah Dasar sebanyak 34 responden (40.5%), sebagai ibu rumah tangga sebanyak 65 responden (77.4%). Mayoritas memiliki kecemasan berat sebanyak 37 responden (44.7%) dan kualitas hidup buruk sebanyak 49 responden (58.8%) dengan p-value 0.001 dengan correlation coefficient 0.765. Simpulan: Adanya hubungan signifikan antara tingkat kecemasan dengan kualitas hidup pada penderita hipertensi pada usia produktif. Mayoritas responden mengalami kecemasan kategori berat yang diikuti dengan rendahnya kualitas hidupnya. Saran: Penderita hipertensi dapat meningkatkan pola hidup sehat, memeriksa kesehatan secara rutin terutama dimensi kesehatan fisik, tidak merasakan putus asa untuk hidup, lebih mendekatkan diri pada Tuhan, serta melakukan komunikasi dengan keluarga dan tetangga.   Kata Kunci: Hipertensi; Kualitas Hidup; Kecemasan; Usia Produktif.